Changes in synaptic transmission of substantia gelatinosa neurons after spinal cord hemisection revealed by analysis using in vivo patch-clamp recording - Kozuka, Yuji (Mol Pain, 2016)
BACKGROUND: After spinal cord injury, central neuropathic pain develops in the majority of spinal cord injury patients. Spinal hemisection in rats, which has been developed as an animal model of spinal cord injury in humans, results in hyperexcitation of spinal dorsal horn neurons soon after the hemisection and thereafter. The hyperexcitation is likely caused by permanent elimination of the descending pain systems. We examined the change in synaptic transmission of substantia gelatinosa neurons following acute spinal hemisection by using an in vivo whole-cell patch-clamp technique. RESULTS: An increased spontaneous action potential firings of substantia gelatinosa neurons was detected in hemisected rats compared with that in control animals. The frequencies and amplitudes of spontaneous excitatory postsynaptic currents and of evoked excitatory postsynaptic currentss in response to non-noxious and noxious stimuli were not different between hemisected and control animals. On the contrary, the amplitude and frequency of spontaneous inhibitory postsynaptic currents of substantia gelatinosa neurons in hemisected animals were significantly smaller and lower, respectively, than those in control animals (P < 0.01). Large amplitude and high-frequency spontaneous inhibitory postsynaptic currents, which could not be elicited by mechanical stimuli, were seen in 44% of substantia gelatinosa neurons in control animals but only in 17% of substantia gelatinosa neurons in hemisected animals. In control animals, such large amplitude spontaneous inhibitory postsynaptic currents were suppressed by spinal application of tetrodotoxin (1 µM). Cervical application of lidocaine (2%, 10 µl) also inhibited such large amplitude of inhibitory postsynaptic currents. The proportion of multi-receptive substantia gelatinosa neurons, which exhibit action potential firing in response to non-noxious and noxious stimuli, was much larger in hemisected animals than in control animals. CONCLUSIONS: These suggest that substantia gelatinosa neurons receive tonic inhibition by spinal inhibitory interneurons which generate persistent action potentials. Spinal hemisection results in hyperexcitation of substantia gelatinosa neurons at least in part by eliminating the tonic descending control of spinal inhibitory interneurons from supraspinal levels.